Pathological Activity in Mediodorsal Thalamus of Rats with Spinal Cord Injury Pain - Whitt, Jessica L. (Society for Neuroscience, 2013)
Spinal cord injury (SCI) results not only in motor deficits, but produces, in many patients, excruciating chronic pain (SCI pain). We have previously shown, in a rodent model, that SCI causes suppression of activity in the GABAergic nucleus, the zona incerta (ZI), and concomitant increased activity in one of its main targets, the posterior nucleus of the thalamus (PO); the increased PO activity is correlated with the maintenance and expression of hyperalgesia after SCI. Here, we test the hypothesis that SCI causes a similar pathological increase in other thalamic nuclei regulated by the ZI, specifically the mediodorsal thalamus (MD), which is involved in the emotional-affective aspects of pain. We recorded single and multiunit activity from MD of either anesthetized or awake rats, and compared data from rats with SCI with data from sham-operated controls (anesthetized experiments) or with data from the same animals prelesion (awake experiments). Consistent with our hypothesis, MD neurons from rats with SCI show significant increases in spontaneous firing rates and in the magnitude and duration of responses to noxious stimuli. In a subset of anesthetized animals, similar changes in activity of MD neurons were produced by pharmacologically inactivating ZI in naive rats, suggesting that the changes in the MD after SCI are related to suppressed inhibition from the ZI. These data support our hypothesis that SCI pain results, at least in part, from a loss of inhibition to thalamic nuclei associated with both the sensory-discriminative and emotional-affective components of pain.